IMPLIKASI KEPEMIMPINAN DISTRIBUTED KEPALA SEKOLAH MENENGAH ATAS NEGERI SENDAWAR TERHADAP PERAN KEPALA SEKOLAH - Elita Sumarni; Husaini Usman; Edi Rahmad (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
The purposes this study to find the implications of distributed leadership on the role of principal qualitative research approach with the type of phenomenology used in this study. The research instrument is the researcher himself. Key informant is the principal. Research respondents were deputy principals, homeroom teachers, and administrative staff. Data were collected through in-depth interviews, participant observation, and documentation studies. Data analysis techniques using Miles, Huberman, and Saldana models. Data validity is done through credibility, dependability, transferability, and confirmability. The results of the study found that the distributed leadership implications of the role of the principal are: delegators, democrats, participators, facilitators, team leaders, do not show the greatest, not as heroes, collaborators, coordinators, communicators, evaluators, priority scales, empowerers and counselors